EVALUASI KEBIJAKAN TAMBAHAN PENGHASILAN PEGAWAI (TPP) DALAM MENINGKATKAN DISIPLIN PEGAWAI NEGERI SIPIL DI KOTA BANJAR - Ririn Yulianti Yulianti (Universitas Indo Global Mandiri, 2022)
ABSTRACT The purpose of this study is to find out and analyze how the Evaluation of Perwal Policy Number 4 of 2016 concerning Additional Employee Income (TPP) at the Community Empowerment, Village, National Unity, and Political Office of Banjar City uses the policy evaluation theory of William Dunn. This study used qualitative research methods. Determination of informants using a purposive sampling technique. The results of the study on the effectiveness criteria found that there were positive changes for increasing discipline; on the efficiency criteria, the aspect of TPP assessment is based on finger scans without being supported by manual attendance, so it is concluded that it is not efficient; on the criteria of adequacy, enforcement of regulations regarding TPP has met the criteria of adequacy; on the criteria of equity, the distribution of information is quite good. This is because it is equipped with supporting facilities and firmness of action; on the criteria of responsiveness, TPP is given based on the number of employee work attendance, not yet based on employee performance; on the criteria of accuracy, the majority of employees agree with the TPP Perwal with sanctions that have been applied due to a shared commitment and enough to provide positive value for change. Overall, the Perwal policy No. 4 of 2016 regarding TPP in improving civil servant discipline has resulted in positive changes for increasing discipline.This is because of the firmness of the Head of Service in implementing the rules. We also found that the obstacle to implementing Perwal No. 4/2016 is the mindset of employees due to a lack of understanding of the rights and obligations of civil servants. Efforts are being made to further improve employee discipline, namely through tiered coaching and sanctions for cutting TPP. Keywords : Policy Evaluation, Additional Income, Civil Servant Discipline ABSTRAK Tujuan penelitian ini untuk mengetahui dan menganalisa bagaimana Evaluasi Kebijakan Perwal Nomor 4 tahun 2016 tentang Tambahan Penghasilan Pegawai (TPP) di Dinas Pemberdayaan Masyarakat, Desa, Kesatuan Bangsa dan Politik Kota Banjar dengan menggunakan teori evaluasi kebijakan dari William Dunn. Penelitian ini menggunakan metode penelitian kualitatif. Penentuan informan menggunakan teknik purposive sampling. Hasil penelitian pada kriteria efektivitas ditemukan bahwa terdapat perubahan positif bagi peningkatan disiplin; pada kriteria efieisensi, aspek penilaian TPP berdasarkan finger scan tanpa di dukung absensi manual, sehingga disimpulkan belum efisien; pada kriteria kecukupan, penegakan perwal tentang TPP telah memenuhi kriteria kecukupan; pada kriteria pemerataan, pemerataan informasi cukup baik hal ini karena dilengkapi sarana pendukung dan ketegasan tindakan; pada kriteria responsivitas, TPP diberikan dengan berdasarkan angka kehadiran kerja pegawai belum berbasis kinerja pegawai; pada kriteria ketepatan, mayoritas pegawai setuju dengan adanya Perwal TPP dengan sanksi yang telah diterapkan karena adanya komitmen bersama dan cukup memberikan nilai perubahan secara positif. Secara keseluruhan dapat disimpulkan bahwa kebijakan Perwal Nomor 4 Tahun 2016 tentang TPP dalam meningkatkan disiplin PNS telah membawa perubahan positif bagi peningkatan disiplin. Hal ini karena adanya ketegasan Kepala Dinas dalam menerapkan aturan. Kami juga mendapati bahwa kendala penerapan Perwal Nomor 4 Tahun 2016 yaitu pola pikir pegawai akibat kurangnya pemahaman tentang hak dan kewajiban sebagai PNS. Upaya yang dilakukan untuk lebih meningkatkan disiplin pegawai yaitu pembinaan berjenjang dan sanksi pemotongan TPP . Kata Kunci : Evaluasi kebijakan, Tambahan Penghasilan , Kedisiplinan PNS